Peculiar Morphology of Montipora millepora Reveals Interspecific Competition for Space Among Two Other Major Foundation Species in Jeju Waters, South Korea - Anna B. Jöst; Garance Perrois; Leonard Pons; Sun Kyeong Choi; Seonggil Go; Taihun Kim (Diversity, 2025)
An atypical surface shape was observed in encrusting coral colonies of Montipora millepora. Initial assumptions on their origin focused on the presence of epibiotic intermediate habitat formers, such as coral-dwelling and -boring organisms. However, further investigations revealed their origin to also be substrate shape-related, prompted by overgrowing other foundation species. The unusual bumps stemmed from encrusting over specimens of the coral Alveopora japonica, and the forked, tube-like structures over holdfasts of the brown alga Ecklonia cava. Spatial distribution patterns and interspecific competition are briefly reviewed. Potential effects of morphological changes for Montipora species identification, as well as implications of altered topography in general, are mentioned.